2018
DOI: 10.1186/s12913-018-3437-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effectiveness and mechanisms of a social prescribing service: a mixed method analysis

Abstract: BackgroundEvidence of the effectiveness of social prescribing is inconclusive causing commissioning challenges. This research focusses on a social prescribing scheme in Northern England which deploys ‘Wellbeing Coordinators’ who offer support to individuals, providing advice on local groups and services in their community. The research sought to understand the outcomes of the service and, in addition, the processes which supported delivery.MethodsQuantitative data was gathered from service users at the point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
211
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(225 citation statements)
references
References 17 publications
6
211
0
8
Order By: Relevance
“…Two-thirds of service-users were female; reflecting existing research that women are more likely to seek support for loneliness (Vandervoort, 2012). Woodall et al (2018) suggested males experience greater benefits from social prescribing than females, however, this study did not identify any differences between genders in respect of changes in loneliness. Service-users under 50 years old appeared to be more likely to experience improvements in loneliness;…”
Section: Discussionmentioning
confidence: 49%
“…Two-thirds of service-users were female; reflecting existing research that women are more likely to seek support for loneliness (Vandervoort, 2012). Woodall et al (2018) suggested males experience greater benefits from social prescribing than females, however, this study did not identify any differences between genders in respect of changes in loneliness. Service-users under 50 years old appeared to be more likely to experience improvements in loneliness;…”
Section: Discussionmentioning
confidence: 49%
“…1 The prescription can take many forms, depending on the community and resources available and patient's needs, but can include a knitting circle, walking group, bereavement support group, or volunteering. Multiple studies indicate that these prescriptions improve social inclusion [2][3][4][5] , mental well-being, 6 physical activity levels, 7 and selfmanagement of health. 8,9 However, beyond identifying the impact of these prescriptions, it is equally important to understand how SP as a process facilitates these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The person or role prescribing the service can differ from country to country as well as within one country depending on the organisation. Prescribed activities can fall within ‘social’, ‘physical’ or ‘economic’ categories [ 24 ] and aim to improve self-care within the community [ 25 ]. The literature describes the characteristics of social prescription, stakeholders and models of delivery [ 23 , 24 , 25 , 26 ].…”
Section: Case Study 2: Social Prescribing Supporting Social Connecmentioning
confidence: 99%
“…Prescribed activities can fall within ‘social’, ‘physical’ or ‘economic’ categories [ 24 ] and aim to improve self-care within the community [ 25 ]. The literature describes the characteristics of social prescription, stakeholders and models of delivery [ 23 , 24 , 25 , 26 ]. Accordingly, the health client journey involves general practitioners working with health clients to determine their level of wellbeing and social interests.…”
Section: Case Study 2: Social Prescribing Supporting Social Connecmentioning
confidence: 99%
See 1 more Smart Citation